Perception of Creativity among Secondary Level Mathematics Teachers: A Qualitative Analysis - Sharan, Neel Kamal (Voices of Teachers and Teacher Educators, 2020)
Children are the future of a nation and creative thinking is an investment in a country’s future. It influences almost all human activities. Hence, the teachers must understand and appreciate the importance of creative thinking and apply it in their teaching. The present paper was developed to gain an insight into the perception of secondary school mathematics teachers about creativity in mathematics. All the teachers agreed that creativity is important for teachers and the students. However, the data show a real picture of their knowledge and use of creativity in the classroom. Approximately 10 teachers, 5 U.P. board teachers, and 5 CBSE board teachers of Varanasi district participated and shared their viewpoint on mathematical creativity. For most of them, creativity in mathematics is only confined to the use of teaching aids and models. Their responses also show which of the activities they adopted by them in their teaching were considered being creative by them.